Gênero, família e escola : a homomaternidade na sala de aula - Palma, Yáskara Arrial (2014)
This thesis proposes a reflection on the relationship between homomaternal families and schools nowadays. Objective: To investigate the relationships between homomaternal families and the school context, identifying and understanding how the dialogue between them and also between some public policy occurs. Method: two qualitative and exploratory studies were performed which resulted in four articles. The first study was a documental review of the National Curriculum Parameters (PCN), the Brazil Without Homophobia Program and the National Human Rights Plans I, II and III. Narrative interviews were used to conduct the second study, searching for lesbian mothers had eleven children and adolescents of school age, plus four pedagogical supervisors. In both studies, we used discourse analysis from the perspective of feminist studies of gender and Socio-Historical Social Psychology to perform the analysis. Results: It was possible to identify the importance of creating public policies to visualize the LGBT public education, but they are not enough measures to contribute effectively in transforming the school reality. Mothers feel accepted and understood in the chosen schools. Despite presenting very wide understandings of what is considered family, pedagogical supervisors still carry on their discourses crossings of heteronormativity and patriarchy still in effect. Conclusion: The school is changing, but issues such as sexual orientation are still treated in a non-visualized way and in an individualized manner. It becomes increasingly urgent that schools open space for marginalized subjects to have a voice and be heard.